2016
DOI: 10.3402/fnr.v60.30888
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and histopathological effects of sleeve gastrectomy and gastric plication: an experimental rodent model

Abstract: IntroductionObesity has recently become a major health problem, and researchers have been directed to work toward the development of surgical techniques, with new mediators playing an important role in nutrition. Gastric plication (GP) and sleeve gastrectomy (SG) have become popular recently. These are widely used techniques in bariatric surgery.ObjectivesIn this study, we aimed to compare the efficiency of SG and GP techniques on rats.MethodsWistar-Hannover rats (n=18) were divided into three equal groups, na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…Gastrin is secreted by antral G cells of the stomach, and previous studies also demonstrated that ghrelin was significantly reduced after GP and SG surgeries. Therefore, our results are consistent with previous studies [28].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Gastrin is secreted by antral G cells of the stomach, and previous studies also demonstrated that ghrelin was significantly reduced after GP and SG surgeries. Therefore, our results are consistent with previous studies [28].…”
Section: Discussionsupporting
confidence: 94%
“…2A). However, according to other studies, GP may not be as effective as SG in terms of total weight loss [28].…”
Section: Discussionmentioning
confidence: 88%
“…Certainly, VSG and GP have been investigated in other animal studies and in human studies. Two recent studies contradict the equivalency identified by Ye et al [5,6]. In both studies, VSG was superior to GP in weight loss.…”
Section: Editorial Commentmentioning
confidence: 80%
“…In both studies, VSG was superior to GP in weight loss. In rats, Gulcicek et al [5] found equivalent changes in ghrelin and leptin after both procedures. In humans, metabolic parameters were equivalently improved after both operations, but VSG resulted in more significant early reduction in ghrelin [6].…”
Section: Editorial Commentmentioning
confidence: 98%
“…The only proven long-term treatment for severe obesity on a population level is the surgical modification of the gastrointestinal anatomy to induce weight loss, termed bariatric surgery 4 . Bariatric surgery, also called weight loss surgery or metabolic surgery, was introduced 50 years ago to provide drastic weight loss in morbidly obese patients 5,6 , and its use is currently increasing to treat patients with high adiposity, or occasionally for metabolic benefits 7 . The most successful types of bariatric surgery involve limiting the absorption of nutrients (malabsorption), reducing the size of the stomach to decrease the total nutrient intake (restriction), and reducing hunger and satiety by altering gut hormones (metabolic) 3 .…”
Section: Introductionmentioning
confidence: 99%